Adams and Eves: The Gender Gap in Economics Majors - Graziella Bertocchi; Luca Bonacini; Marina Murat (Global Labor Organization (GLO), 2021)
We investigate the gender gap in Economics among bachelor's and master's grad- uates in Italy between 2010 and 2019. First we establish that being female exerts a negative impact on the choice to major in Economics: at the bachelor level, only 73 women graduate in Economics for every 100 men, with the mathematical con- tent of high school curricula as the key driver of the effect and a persistence of the gap at the master level. Second, within a full menu of major choices, Economics displays the largest gap, followed by STEM and then Business Economics. Third, decomposition analyses expose a unique role for the math background in driving the Economics gender gap relative to other fields. Fourth, a triple difference analysis of a high school reform shows that an increase in the math content of traditionally low math curricula caused an increase in the Economics gender gap among treated students.
Keywords: A22; I23; J16; 330; Education Gender Gap; Economics; Higher Education; Business Economics; Major Choice; Major Switching; Mathematics; Stereotypes